Blockchain and smart contracts - SCHILLEBEECKX, Simon J.D. (Institutional Knowledge at Singapore Management University, 2016)
This discussion paper covers and develops the ideas discussed during the Roundtable Discussion on Blockchain and Smart Contracts, jointly organised by the Singapore CFO institute and the Sim Kee Boon Institute for Financial Economics (SKBI) at Singapore Management University (SMU) on the 29th of June, 2016. The discussion was moderated by: Professor David Lee Kuo Chen (SKBI & SMU) and Mr Loh Uantchern (Chief Executive Singapore Accountancy Commission).